Photodegradation in Encapsulated Silole‐Based Polymer: PCBM Solar Cells Investigated using Transient Absorption Spectroscopy and Charge Extraction Measurements. Issue 11 (11th July 2013) - Clarke, Tracey M.; Lungenschmied, Christoph; Peet, Jeff; Drolet, Nicolas; Sunahara, Kenji; Furube, Akihiro; Mozer, Attila J.
Abstract Light induced degradation has been observed in the performance of organic solar cells in the absence of oxygen and a detailed analysis of the effect of this photodegradation on optical and electrical features has been accomplished. This photodegradation study has been performed on encapsulated photovoltaic blend devices comprised of the silole‐based donor–acceptor polymer KP115 blended with [6, 6]‐phenyl C61‐butyric acid methyl ester (PCBM). Photodegradation induces an almost 20% decrease in power conversion efficiency, primarily as a result of a reduction in short circuit current, JSC. The initial burn‐in phase of the photodegradation has been examined using a combination of transient absorption spectroscopy and charge extraction measurements, including photo‐CELIV (charge extraction by linearly increasing voltage) and time‐resolved charge extraction using a nanosecond switch. These measurements reveal a bimodal KP115 polaron population, comprised of both delocalised and localised/trapped charge carriers. The photodegradation results are consistent with an alteration of this bimodal KP115 polaron population, with the polarons becoming trapped in a broader, deeper density of localised states. Under laser illumination and at open circuit conditions, this enhanced trapping after light soaking inhibits charges from undergoing bimolecular recombination, leading to higher extracted charge densities at long times. At the lower charge densities operating at short circuit conditions and under continuous white light illumination, where bimolecular recombination is much less significant, the JSC decreases after light soaking due to a reduction in the efficiency of trapped charge carrier extraction.